Dual-track interest rates and the conduct of monetary policy in China - Dong He; Honglin Wang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
China has a dual-track interest-rate system: bank deposit and lending rates are regulated while money and bond rates are market-determined. The central bank also imposes an indicative target, which may not be binding at all times, for total credit in the banking system. We develop and calibrate a theoretical model to illustrate the conduct of monetary policy within the framework of dual-track interest rates and a juxtaposition of price- and quantity-based policy instruments. We model the transmission of monetary policy instruments to market interest rates, which, together with the quantitative credit target in the banking system, ultimately are the means by which monetary policy affects the real economy. The model shows that market interest rates are most sensitive to changes in the benchmark deposit interest rates, significantly responsive to changes in the reserve requirements, but not particularly reactive to open market operations. These theoretical results are verified and supported by both linear and GARCH models using daily money and bond market data. Overall, the findings of this study help us to understand why the central bank conducts monetary policy in China the way it does, using a combination of price and quantitative instruments with differing degrees of potency in terms of their influence on the cost of credit. ?
URN:NBN:fi:bof-201408071995
Keywords: 330